Ответы и объяснения

2011-02-08T14:10:24+00:00

(a^2-a+1)^2 -4a(a^2+1)=0;

((а²+1) -а)² - 4а(а²+1)=0;

(а²+1)² - 2а(а²+1) + а² - 4а(а²+1)=0;

(а²+1)² - 6а(а²+1) + а²=0;

а⁴ + 2а²+1 - 6а³ - 6а + а²=0;

а⁴ - 6а³ +3а² - 6а +1=0;

а² - 6а + 3 - 6/а + 1/а²=0;

(а²-2+1/а²) - 6(а-1/а) +5 =0;

(а- 1/а)² - 6(а-1/а) +1=0

Для решения обозначим,что а-1/а=х, тогда:

х² - 6х + 5=0.

D= 36-20=16.

х= \frac{-b +- \sqrt{D}}{2}.

х₁=\frac{6 + \sqrt{16}}{2}=3 +  2=5
х₂=\frac{6 - \sqrt{16}}{2}=3 -  2=1.

Решаем 2 уравнения:

а-1/а=5 и а-1/а=1

1) а-1/а=5;

а² -5а -а=0;

D= 25+4=29;

а₁=( 5+√29)/2;   а₂=( 5-√29)/2;

2)а-1/а=1;

а² -а -а=0;

D= 1+4=5;

а₃=( 1+√5)/2;   а₄=( 1-√5)/2;

Ответ: ( 5+√29)/2; ( 5-√29)/2;( 1+√5)/2;( 1-√5)/2.